Role of Magnetic Resonance Imaging in the Diagnosis of Glomus Tumor - Küçük, Levent; Özdemir, Oğuz; Coşkunol, Erhan; Çetinkaya, Seyithan; Keçeci, Burçin; Öztürk, Anıl Murat (Fırat University, 2011)
Objective: Glomus tumor of the hand, most often seen in the tips of the fingers, is a lesion originating from the glomus bodies. Glomus tumor is a rare tumor of the hand. The main complaints of the patients are pain, local tenderness and cold intolerance. Glomus tumor is most often diagnosed clinically. The purpose of this study is to investigate the role of magnetic resonance imaging in the diagnostic algorithm of glomus tumor. Materials and Methods: 80 patients who underwent surgery in our clinic between the years 1978-2009 with a diagnosis of glomus tumor were evaluated retrospectively. Preoperative MRI was performed on 22 patients. The diagnosis was confirmed histopathologically in all patients. Results: 4 of 22 patients had surgery despite a normal MRI, and tumor was diagnosed histopathologically. Conclusion: It should be kept in mind that magnetic resonance imaging techniques can give false negative results in diagnosis of glomus tumor of the hand. Surgery decision should be based on clinical history and physical examination. Nevertheless magnetic resonance imaging is a valuable diagnostic tool to confirm the diagnosis and to decide surgical exposure.

Amaç: Glomus tümörü vücuda sıklıkla el parmaklarının uçlarında görülen, glomus cisimciklerinden köken alan bir lezyondur. Nadir bir el tümörüdür. Olguların başlıca şikayetleri ağrı, lokal hassasiyet ve soğuk intoleransıdır. Tanısı anamnez, fizik muayene ve görüntüleme yöntemleriyle konur. Bu çalışmanın amacı glomus tümörlerinin tanısal algoritmasında manyetik rezonans görüntüleme (MRG) yönteminin yerini araştırmaktır. Gereç ve Yöntemler: Kliniğimizde 1978-2009 yılları arasında glomus tümörü ön tanısıyla ameliyat edilen 80 olgu içerisinden ameliyat öncesi MRG tetkiki yapılan 22 olgu geriye dönük olarak değerlendirilmeye alınmıştır. Tüm olgularda histopatolojik doğrulama yapılmıştır. Bulgular: 22 hastanın 4'ünde MRG normal olmasına rağmen ameliyat edilmiş ve glomus tümörü tanısı histopatolojik olarak konmuştur. Sonuç: Glomus tümörünün tanısında kullanılan manyetik rezonans görüntüleme yönteminin yanlış negatif sonuç verebileceği akılda tutularak mutlak cerrahi endikasyon kriteri olarak kullanılmaması sonucuna ulaşıldı. Anamnez ve fizik muayene temel alınarak cerrahi endikasyon konmalıdır. Bununla birlikte MRG tanıyı destekleyebilecek ve tedavi planlamasında yol gösterebilecek değerli bir yardımcı tanı aracı olarak kullanılabilir.
Glomus Tümörü Tanısında Manyetik Rezonans Görüntülemenin Yeri